PEMBANGUNAN PERDESAAN BERKELANJUTAN MELALUI MODEL PENGEMBANGAN AGROPOLITAN - Sugimin Pranoto; Syamsul Ma'arif; Surjono H. Sutjahjo; Hermanto Siregar (Jurnal Manajemen & Agribisnis, 2006)
The development implemented throughoutall this time still reveals an unbalanced development between the urban andrural area. This has occured due to the development policy that is lessfavorable toward the development of rural areas causing various  problems of imbalances (inequalities) ofwelfares among the regions. In addition, the failures of development in therural areas have caused backwash effect, and the domination of capital marketand welfares have been mostly possesed by the urban dwellers. The conditionof  rural communities have become moredeteriorated, poorer, and the level of unemployment becoming higher. Thedevelopment of agropolitan (agro-based area development) is expected to providepositive impact in the effort to empowering the rural community, reducingpoverty, and supporting rural economic activities that are environmentallyoriented. This study aims to develop a sustainable rural policy through theagropolitan development model, based on regional analysis, insitutional analysis(ISM), and dynamic system. The agropolitan development is relatively able toimprove the income per capita of the rural population. Dynamic system analysisshowed that the agropolitan model follows the basic pattern of Archetype Limitto Success, with production growth as a leverage factor of the dynamic model.Thus, the policy orientation to improve people's welfare is a policy that ableto improve the quantity and quality of products in a sustainable manner. Theresult of analysis of institutional aspect showed key factors that supportsuccessful agropolitan development which are skilled human resources, businesspartnership and marketing, and the performance of institutions that provideinput. The major constraints faced are small size land ownership and productiveagriculture land conversion, extension services agencies that are not yeteffective, low quality of human resources, business behavior change not easy,and low support of capital institution.